2021
DOI: 10.1101/2021.06.28.450270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optogenetic tools for public goods control in Saccharomyces cerevisiae

Abstract: Microorganisms live in dense and diverse communities, with interactions between cells guiding community development and phenotype. The ability to perturb specific intercellular interactions in space and time provides a powerful route to determining the critical interactions and design rules for microbial communities. Approaches using optogenetic tools to modulate these interactions offer promise, as light can be exquisitely controlled in space and time. We report new plasmids for rapid integration of an optoge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…As mentioned previously, these platforms (unlike microscope-coupled platforms) do not provide precise spatial control over light delivery. But, one can use simple photomasks to achieve a desired spatial-pattern light illumination onto lawns of cells cultured in well plates or petri dishes ( Levskaya et al, 2005 ; Beyer et al, 2015 ; Romano et al, 2021 ; Morales et al, 2021 ). Using illumination through photomasks, the authors in ( Levskaya et al, 2005 ; Romano et al, 2021 ) have also demonstrated creating a high-definition high-contrast chemical image (bacteriograph) of the projected light mask pattern similar to images captured on camera films.…”
Section: Low-volume Culture Platformsmentioning
confidence: 99%
“…As mentioned previously, these platforms (unlike microscope-coupled platforms) do not provide precise spatial control over light delivery. But, one can use simple photomasks to achieve a desired spatial-pattern light illumination onto lawns of cells cultured in well plates or petri dishes ( Levskaya et al, 2005 ; Beyer et al, 2015 ; Romano et al, 2021 ; Morales et al, 2021 ). Using illumination through photomasks, the authors in ( Levskaya et al, 2005 ; Romano et al, 2021 ) have also demonstrated creating a high-definition high-contrast chemical image (bacteriograph) of the projected light mask pattern similar to images captured on camera films.…”
Section: Low-volume Culture Platformsmentioning
confidence: 99%